Study on wavelet transform for detecting time arrival of faults wave - Zabidi, Muhammad Amaluddin (2017)
The fault generated transient traveling waves are wide band signals which cover the whole frequency range. The detection of faults location appearing in a power system is extremely important. Estimation and determination of fault location in power transmission system are very vital to repair the fault damage happen on the apparatus quickly and to restore supply with minimum interruption. The objectives of this thesis is, firstly to measure the accuracy of fault distance based on traveling wave depends on arrival time of fault wave. Secondly, to investigate the types of wavelet transform which is more compatibility to determine the distance of faults. This thesis presents the determination of fault distance on the power transmission line. The cable of the transmission line is modeled in MATLAB Simulink using simpower system tool box. There are two different wavelet transform to be investigated which is by using Coif Let, Haar and Mexican Hat transform. This three type wavelet transform are used to analyze the arrival time of the fault signal. Result between three types wavelet will be compared. This simulation result show that Haar wavelet is suitable and efficient powerful tool to estimate the fault distance when occur on the power transmission system.